First Russian Gastroenterology Olympiad - V. T. Ivashkin; E. K. Baranskaya; Yu. O. Shulpekova; S. S. Kardasheva; N. L. Dzhakhaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
On October 21, 22, 23, 2022, within the framework of the 122nd International Session of the National School of Gastroenterology, Hepatology (NSGH) of the Russian Gastroenterological Association (RGA), the First Russian Gastroenterology Olympiad was held.